Application Of The TOPSIS Method For Prioritizing The Procurement Of Goods Stock Based On Sales Rates In Alfamidi Sadabuan - Alya Hutri Yani; Aulia Ramdhani; Lela Budiarti (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2026)
This study aims to design a Decision Support System (DSS) to objectively determine restocking priorities in Dawa Supermarket. The main challenge faced is the difficulty in identifying which items should be prioritized for reordering amidst fluctuating sales levels and product diversity, which poses the risk of understocking or overstocking. The method used is the Technique of Preference Ordering by Similarity to the Ideal Solution (TOPSIS), utilizing evaluation criteria such as sales levels, remaining stock, lead time, and item prices. The calculation process involves identifying alternatives with the shortest distance from the positive ideal solution and the longest distance from the negative ideal solution to produce a final preference value. The results show that the application of the TOPSIS method provides more accurate and measurable recommendations for procurement priorities, thereby assisting Dawa Supermarket management in optimizing shelf availability and improving working capital turnover efficiency